Prediction of insignificant prostate cancer in men with stage T1c disease - (:unkn) unknown (My University, 2000)
Objective: In this retrospective study, we evaluated the ability of preoperative parameters to predict tumor significance in men with stage T1c disease who underwent radical retropubic prostatectomy. Patients and Methods: A total of 26 consecutive patients who underwent radical retropubic prostatectomy owing to clinically localized disease fulfilled the criteria for insignificant cancer namely PSA density lower or equal to 0.10, presence of Gleason grade < 4 (Gleason sum ≤ 6), number of cores (< 3) involved with cancer, and tumor percentage less than 50% for insignificant prostate cancer. Additionally, we only included the patients with a PSA level of less than 10 ng/ml. Results: According to pathological examination, 6 (23%) of these patients had bilateral (pT2c) disease, 5 (19.2%) had extracapsular disease (pT3a-b), 2 (7.7%) had seminal vesicle (pT3c) involvement and 2 (7.7%) had positive surgical margins. Consequently, at least 50% of these cases were significant cancer. Conclusion: In conclusion, our demonstrated that the patient and the physician must be aware of the variability and insufficiency of these preoperative algorithms for predicting insignificant cancers in discussing treatment alternatives.
Keywords: Insignificant tumor; Prostate cancer; Stage T1c disease